2019
DOI: 10.1159/000496354
|View full text |Cite
|
Sign up to set email alerts
|

Growth Disturbances in Childhood Cancer Survivors

Abstract: Survival from childhood cancer has improved dramatically over the last few decades, resulting in an increased need to address the long-term follow-up and care of childhood cancer survivors. Appropriate linear growth is an important measure of health, with alterations of growth in children and short adult height in those who have completed growth serving as potential indicators of the sequelae of the underlying diagnosis or the cancer treatments. It is therefore critical that clinicians, particularly endocrinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 115 publications
3
2
0
Order By: Relevance
“…Patients with medulloblastoma diagnosis experienced steep growth loss after diagnosis, reflecting the severity of the disease and its treatments. The negative impact of these factors on growth has also been shown by others [9,[30][31][32].…”
Section: Plos Onesupporting
confidence: 64%
See 1 more Smart Citation
“…Patients with medulloblastoma diagnosis experienced steep growth loss after diagnosis, reflecting the severity of the disease and its treatments. The negative impact of these factors on growth has also been shown by others [9,[30][31][32].…”
Section: Plos Onesupporting
confidence: 64%
“…This often results in compromised adult height, especially when not treated accurately [4][5][6][7]. Previous studies have shown low adult height in long-term brain tumor survivors [8], but the knowledge of the disease's impact on growth potential, especially before diagnosis, is more limited [9]. Still, longitudinal studies on growth patterns during different growth periods in this patient group are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Acute Lymphoblastic Leukemia survivors appear to present a deficit in the Z-score of height during chemotherapy and an increase in the BMI indexes, which is not followed by an appropriate catch up with growth [24]. Evaluating the Height per Age Index most of the patients had an adequate height for their age similar to the data found in another study [17].…”
Section: Discussionsupporting
confidence: 74%
“…In this study, the height SDS of survivors was inversely correlated to the WHO degree of the tumor. And, like other groups ( 49 ) we could show that growth was more stunted in children who received irradiation. Irradiated patients also displayed a higher number of impaired endocrine axes, pointing toward the intertwined effects of irradiation, the resulting hormonal deficiencies and the tumor stage on growth in children and adolescents.…”
Section: Discussionsupporting
confidence: 71%